2009
DOI: 10.2334/josnusd.51.333
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of mentally disabled subjects in India

Abstract: The aim of the study was to determine the oral health status and investigate the association of oral health status with various socio-demographic (age, gender, parent's education, income) and clinical variables (aetiology for mental disability and IQ level) among mentally disabled subjects. The study sample comprised 225 mentally retarded subjects aged 12-30 years attending a special school in Udaipur, India. Caries status, oral hygiene status and periodontal status were assessed by DMFT Index, Simplified Oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
2
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 24 publications
9
60
2
14
Order By: Relevance
“…Las enfermedades orales son uno de los mayores problemas de salud en personas con discapacidad 6,7 , debido a que la prevalencia y severidad de estas son mayores a las de la población general 4,6 . A pesar de tener derecho a los mismos estándares de salud y atención, se considera que la salud oral es una de las mayores necesidades de salud no satisfechas en esta población 8,9 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Las enfermedades orales son uno de los mayores problemas de salud en personas con discapacidad 6,7 , debido a que la prevalencia y severidad de estas son mayores a las de la población general 4,6 . A pesar de tener derecho a los mismos estándares de salud y atención, se considera que la salud oral es una de las mayores necesidades de salud no satisfechas en esta población 8,9 .…”
Section: Discussionunclassified
“…De acuerdo a un estudio realizado en India, se concluyó que la experiencia de caries en individuos discapacitados es mayor a la de la población general, y que existe una tendencia a encontrar peores índices de salud oral a medida que la edad aumenta, encontrándose por tanto un mayor COPD en los grupos de mayor edad 4 . Sin embargo, en la población chilena evaluada, los estudiantes con discapacidad intelectual no presentaron mayor experiencia de caries, sino que poseen índices similares (COPD) al de la población general de acuerdo al Diagnóstico Nacional de Salud Dental del Adolescente (1.69 y 1.9 respectivamente a los 12 años de edad) 10 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…2,28,29 The OHI-S scores for the prisoners in the present study were very high compared with the reported OHI scores for physically and mentally handicapped children in the previous studies. 20,30,31 As the age increased, the OHI-S scores also increased, which could be explained by the fact that the cumulative effect of plaque and calculus increases with the age. 2 The increased OHI-S with age conforms with the previous studies.…”
Section: Discussionmentioning
confidence: 99%